Changes in Lymphocyte Composition and Functionality After Intensive Training and Exhausting Exercise in Rats - Estruel-Amades, Sheila; Ruiz-Iglesias, Patricia; Périz, Marta; Franch, Àngels; Pérez-Cano, Francisco J.; Camps-Bossacoma, Mariona; Castell, Margarida (Frontiers in Physiology, 2019)
Exhausting exercise can have a deleterious effect on the immune system. Nevertheless, the impact of exercise intensity on lymphocyte composition and functionality remains uncertain. The aim of this study was to establish the influence of intensive training on lymphoid tissues (blood, thymus, and spleen) in Wistar rats. Two intensive training programs were performed: a short program, running twice a day for 2 weeks and ending with a final exhaustion test (S-TE group), and a longer program, including two exhaustion tests plus three runs per week for 5 weeks. After this last training program, samples were obtained 24 h after a regular training session (T group), immediately after an additional exhaustion test (TE group) and 24 h later (TE24 group). The composition of lymphocytes in the blood, thymus, and spleen, the function of spleen cells and serum immunoglobulins were determined. In the blood, only the TE group modified lymphocyte proportions. Mature thymocytes’ proportions decreased in tissues obtained just after exhaustion. There was a lower percentage of spleen NK and NKT cells after the longer training program. In these rats, the T group showed a reduced lymphoproliferative activity, but it was enhanced immediately after the final exhaustion. Cytokine secretion was modified after the longer training (T group), which decreased IFN-γ and IL-10 secretion but increased that of IL-6. Higher serum IgG concentrations after the longer training program were detected. In conclusion, the intensive training for 5 weeks changed the lymphocyte distribution among primary and secondary lymphoid tissues and modified their function.